Effects of statins on serum sCD40, sCD146 and PAPP-An in patients with coronary heart disease: serum sCD40, sCD146 and PAPP-An in patients with coronary heart disease - Li, Huawen; Zhou, Xia; Zhu, Wenyan; Zhang, Jing (Journal of Medical Biochemistry, 2025)
0